1440 Health status of brick kiln workers in north east india. (24th April 2018) - Mittal, Ashish; John, J; Pandya, Arati; Gupta, Ruchi; Debbarma, Anima; Sushma, xxx; Yadav, Shambhu
Abstract : Introduction: India produces 200–250 billion clay bricks annually, the second largest producer of clay fired bricks, accounting for more than 10% of global production, in 1 50 000 to 2 00 000 brick kilns. Each brick kiln employs between 250–300 workers, bringing the total number of workers to approximately 20 million, which is roughly 4 per cent of a total of 459 million workers in India, of which almost 40% are women. The Brick Industry in India is characterised by traditional methods of production technology and seasonal work. Methods: The study was done in Tripura, a state in North East India to assess the impact of traditional brick manufacturing technology on the health of the workers. A convenient available sample of 94 workers from 4 brick kilns who have worked for 5 years or more were taken from the total population of 280 (including children) of these kilns. The workers were interviewed to obtain information on the demography and personal habit followed by general physical medical examination, blood test for complete haemogram, random blood sugar levels and pulmonary function test. The data was analysed using MS Office Excel 2007 & Epi. Info 7.2.1.0 version. Results: The average age of workers is 34 years, 27% were female and 73% male workers. 55% worker are loaders, 29% moulders and 7% fire-workers, 75% being migrant workers, 49% being underweight, 51% anaemic, 78% have eosinophilia (younger workers more affected, p value 0.04), 66% have low back pain. Conclusion: Brick kiln workers are suffering from high morbidity in North east India because of their work. This demands urgent attention for the health and safety program that should include regular in-service training emphasising health risk of brick kiln work, preventive measures, technological interventions etc. Health surveillance of workers would be highly beneficial in achieving better health status.